Forkhead box M1 (FoxM1) gene is a new STAT3 transcriptional factor target and is essential for proliferation, survival and DNA repair of K562 cell line. - André L Mencalha; Renata Binato; Gerson M Ferreira; Barbara Du Rocher; Eliana Abdelhay (PLoS ONE, 2012)
The forkhead box (Fox) M1 gene belongs to a superfamily of evolutionarily conserved transcriptional regulators that are involved in a wide range of biological processes, and its deregulation has been implicated in cancer survival, proliferation and chemotherapy resistance. However, the role of FoxM1, the signaling involved in its activation and its role in leukemia are poorly known. Here, we demonstrate by gene promoter analysis, Electrophoretic mobility shift assay (EMSA) and chromatin immunoprecipitation (ChIP) assays that FoxM1 is a new target of the STAT3 transcriptional activator. Additionally, FoxM1 is transcriptionally dependent on STAT3 signaling activation. Furthermore, we verified that FoxM1 is crucial for K562 cell proliferation, cell cycle checkpoints and viability and could be related to chemotherapeutic resistance. By microarray analysis, we determined the signaling pathways related to FoxM1 expression and its role in DNA repair using K562 cells. Our results revealed new signaling involved in FoxM1 expression and its role in leukemic cells that elucidate cellular mechanisms associated with the development of leukemia and disease progression.